(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces a new class of functions between bitopological spaces, namely almost contra-(τ_1,τ_2)p-continuous functions. Moreover, some characterizations and several properties concerning almost contra-(τ_1,τ_2)p-continuous functions are established.